Long-term effects of a multidisciplinary transition intervention from paediatric to adult care in patients with epilepsy. (May 2016) - Geerlings, R.P.J.; Aldenkamp, A.P.; Gottmer-Welschen, L.M.C.; van Staa, A.L.; de Louw, A.J.A.
Highlights: To describe the medical and psychosocial outcome after a transition intervention. Interventions are predictors for improvement in medical outcome and independence. Interventions are strong predictors for the overall psychosocial outcome. Most patients benefit from visiting an epilepsy transition clinic. Abstract: Purpose: To evaluate the long-term effects of a multidisciplinary transition intervention compared to the impact of patient-related intrinsic factors on the improvement in medical and psychosocial outcome. Methods: All patients who visited our multidisciplinary Epilepsy Transition Clinic between March 2012 and September 2014 were invited to participate ( n = 114). Patients were sent one questionnaire and informed consent was obtained. Questions included the patient's level of functioning on three transitional domains and a list with medical health care workers. Previously defined scores on three transitional domains and the risk profile score were re-evaluated. Past and current patient characteristics were compared using descriptive statistics. Discriminant analyses were used to determine the influence of patient-related intrinsic factors (defined as the risk factors from our previous study) and a multidisciplinary transition intervention on the improvement of medical and psychosocial outcome. Results: Sixty-six out of 114 invited participants (57.9%) completed the questionnaire. Discriminant analyses showed that the patient-related intrinsic factors combined proved a strong predictor for improvement in medical outcome (72.7%) and relatively strong for educational/vocational outcome (51.5%). The transition interventions are a relative strong predictor of improvement in medical outcome (56.1%), educational/vocational outcome (53.0%) and improvement in the overall risk score (54.5%). Conclusion: Based on the overall improvement of psychosocial outcome in most patients, and the influence of a transition intervention on medical, educational/vocational outcome and the overall risk score, it is likely that adolescents with epilepsy benefit from visiting a multidisciplinary epilepsy transition clinic.